2001
DOI: 10.1097/00006254-200111000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breastfeeding on Mortality Among HIV-1 Infected Women: A Randomised Trial

Abstract: SummaryBackground-We have completed a randomised clinical trial of breastfeeding and formula feeding to identify the frequency of breastmilk transmission of HIV-1 to infants. However, we also analysed data from this trial to examine the effect of breastfeeding on maternal death rates during 2 years after delivery. We report our findings from this secondary analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 12 publications
(16 reference statements)
2
61
1
1
Order By: Relevance
“…Evaluation of the effectiveness of the nutritional supplement for preventing maternal depletion will be based on weight loss between 4 and 28 weeks post-partum. For this outcome we anticipate that mothers not receiving a supplement will lose 0.17 kg/month and mothers receiving a supplement will lose 0 kg/month with a constant standard deviation 1.32 (32). The study sample size as calculated above has over 90% power to detect a difference of 0.20 kg in mean maternal weight loss from 4 to 28 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the effectiveness of the nutritional supplement for preventing maternal depletion will be based on weight loss between 4 and 28 weeks post-partum. For this outcome we anticipate that mothers not receiving a supplement will lose 0.17 kg/month and mothers receiving a supplement will lose 0 kg/month with a constant standard deviation 1.32 (32). The study sample size as calculated above has over 90% power to detect a difference of 0.20 kg in mean maternal weight loss from 4 to 28 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Producing breast milk of adequate quantity and quality is, however, nutritionally demanding for mothers, particularly for those who have chronic infections. Unless diet during pregnancy and lactation is adequate, prolonged breastfeeding is likely to lead to maternal nutritional depletion (inadequate nutritional intake compared to metabolic needs) (2932). Depletion leading to rapid weight loss may place HIV-infected mothers at greater risk of succumbing to opportunistic infections, indirectly increasing their disease progression and risk of death (32;33).…”
Section: Introductionmentioning
confidence: 99%
“…HIV/AIDS was the leading cause of maternal mortality in the South African Confidential Enquiry into Maternal Deaths in 2000 22. A recent study from Kenya found that mortality among HIV-1 infected mothers was higher in women who breast fed than in women who fed their babies with formula (18 v 6 deaths; log rank test P=0.009) 23. In this study, maternal death was associated with an increased risk of subsequent infant death, and, even after controlling for HIV-1 infection in the infant, it was shown that infants of mothers who died had an eightfold increase in the likelihood of subsequent death.…”
Section: Effect Of Hiv Related Maternal Mortality On Infant Survivalmentioning
confidence: 97%
“…It is unclear how seriously these demands affect their own health. Two studies found that weight loss in HIV-infected mothers during lactation led to higher mortality among these women (15,16), whereas 2 other studies found no association of breastfeeding with mortality (17,18).…”
Section: Introductionmentioning
confidence: 98%